2020
DOI: 10.2478/hukin-2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Morphofunctional Variables Associated with Performance in Crossfit® Competitors

Abstract: CrossFit® is a competitive sport and fitness modality characterized by multiple physical capabilities and multi-joint movements. This study aimed to analyse and classify variables related to CrossFit® competitors’ specific performance. Fifteen male CrossFit® competitors were selected (n = 15; 30.57 ± 5.5 years; 1.76 ± 0.06 m; 78.55 ± 9.12 kg). Mean values were obtained for body mass index (25.3 ± 2.14 kg/m2), 4 skinfolds, 1 repetition maximum in the squat (137.60 ± 19.65 kg) and the bench press (101.67 ± 10.64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…CrossFit is one of the most popular training programs but there is a tremendous lack of research that needs to be fulfilled [ 6 , 8 , 9 , 17 , 18 , 19 ]. Hence, explanations for physiological and morphological predictors require investigation to clarify the physiological indicators of CrossFit sports performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CrossFit is one of the most popular training programs but there is a tremendous lack of research that needs to be fulfilled [ 6 , 8 , 9 , 17 , 18 , 19 ]. Hence, explanations for physiological and morphological predictors require investigation to clarify the physiological indicators of CrossFit sports performance.…”
Section: Discussionmentioning
confidence: 99%
“…In our data, we found 49% and 64% relative 1RM for thrusters and pull-up, respectively, which resulted in a stronger correlation of strength endurance for thrusters and moderate to stronger correlations for maximal strength of thrusters and strength endurance for pull-ups. Rodriguez et al [ 6 ] reported a correlation between the squat absolute strength and FRAN ( r = 0.528; p < 0.05) due to its similarity to the thruster movement. Our results showed that coaches should prioritize these variables to improve the performance of their athletes during training periodization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations